MUC5AC mucin release from human airways in vitro: Effects of indomethacin and Bay X1005 - Patricia Roger; Jean-Pierre Gascard; Jacques Bara; Vincent Thomas de Montpreville; Charles Brink (Mediators of Inflammation)
Background: Increased secretion of mucus is a hallmark of many respiratory diseases and contributes significantly to the airflow limitation experienced by many patients. While the current pharmacological approach to reducing mucus and sputum production in patients is limited, clinical studies have suggested that drugs which inhibit the cyclooxygenase and/or 5-lipoxygenase enzymatic pathways may reduce secretory activity in patients with airway disease.